Effects of hypoxia-induced gill remodelling on the innervation and distribution of ionocytes in the gill of goldfish, Carassius auratus - Tzaneva, Velislava; Vadeboncoeur, Claudia; Ting, Jaimee; Perry, Steve F (Université d'Ottawa | University of Ottawa, 2013)
The presence of an interlamellar cell mass (ILCM) on the gills of goldfish acclimated to 7°C leads to preferential distribution of branchial ionocytes to the distal edges of the ILCM, where they are likely to remain in contact with the water and hence remain functional. Upon exposure to hypoxia, the ILCM retracts, and the ionocytes become localized to the lamellar surfaces and on the filament epithelium, owing to their migration and the differentiation of new ionocytes from progenitor cells. Here we demonstrate that the majority of the ionocytes receive neuronal innervation, which led us to assess the consequences of ionocyte migration and differentiation during hypoxic gill remodelling on the pattern and extent of ionocyte neuronal innervation. Normoxic 7°C goldfish (ILCM present) possessed significantly greater numbers of ionocytes/mm(2) (951.2 ± 94.3) than their 25°C conspecifics (ILCM absent; 363.1 ± 49.6) but a statistically lower percentage of innervated ionocytes (83.1% ± 1.0% compared with 87.8% ± 1.3%). After 1 week of exposure of goldfish to hypoxia, the pool of branchial ionocytes was composed largely of pre-existing migrating cells (555.6 ± 38.1/mm(2)) and to a lesser extent newly formed ionocytes (226.7 ± 15.1/mm(2)). The percentage of new (relative to pre-existing) ionocytes remained relatively constant (at ∼30%) after 1 or 2 weeks of normoxic recovery. After hypoxia, pre-existing ionocytes expressed a greater percentage of innervation than newly formed ionocytes in all treatment groups; however, their percentage innervation steadily decreased over 2 weeks of normoxic recovery.
Keywords: ILCM; hypoxia; gill remodelling; gill epithelia